Improving The Quality Of Information, Communication Technology Based Theology Learning - Purim _ Marbun; Alex Frans Nathanael Nasution (SISFOTENIKA, 2021)
This paper was motivated by a problem of poor understanding and the implementation of information communication technology-based learning in Christian theological schools, particularly in the use of various resources in improving the quality of learning. In many additions, lecturers have not maximally used information communication technology massively due to the lack of facilities and infrastructures as well as the inaccurate technical ability using it. The research method in this writing is qualitative literature. Researchers will be exploring many sources related to this topic in question and analyze the subjects to the research title. Result of this study provides input and strategies on how to use information communication and technology in learning Christian theology in order to achieve the quality of learning.